Seasonal alterations in blood biochemical parameters among zebu and crossbred cattle. Issue 12 (2nd December 2022) - Tejaswi, V.; Bosco, J.; Verma, V.; Anjali,; Pathak, M.C; Samad, H.A.; Tiwari, A.K.; Chouhan, V.S.; Maurya, V.P.; Sarkar, M.; Singh, Gyanendra
ABSTRACT: The present study was undertaken to evaluate the adaptive capability between native and crossbred cattle during summer and winter using certain serum biochemical variables. Eighteen apparently healthy lactating cattle of same age group between 4 and 5 years were selected and divided into three groups ( n = 6) with consideration of breed as Group I: Crossbred, Group II: Tharparkar and Group III: Sahiwal. Blood samples were collected from each animal for 6 weeks during summer and 6 weeks in winter. A significant high values of all the biochemical parameters under the study, viz., total protien, albumin, glucose, blood urea nitrogen, creatinine and cholesterol were noted in summer in comparision to winter within each group. Also, Group III showed higher values of glucose, creatinine, cholesterol both in summer and winter when compared to the other study groups. Our results suggested that the heat stress has a more deleterious effect on the plasma biochemical parameters irrespective of the breed. In addition, among native breeds and crossbred, the native cattle showed minimum biochemical variations with the season and thus can be considered as higher thermo-adaptable than the crossbred cattle.